Polyalthia longifolia Methanolic Leaf Extracts (PLME) induce apoptosis, cell cycle arrest and mitochondrial potential depolarization by possibly modulating the redox status in hela cells - Vijayarathna, Soundararajan; Oon, Chern Ein; Chen, Yeng; Kanwar, Jagat R.; Sasidharan, Sreenivasan (Elsevier, 2017)
Medicinal plants have been accepted as a gold mine, with respect to the diversity of their phytochemicals. Many medicinal plants extracts are potential anticancer agents. Polyalthia longifolia var. angustifolia Thw. (Annonaceae) is one of the most significant native medicinal plants and is found throughout Malaysia. Hence, the present study was intended to assess the anticancer properties of P. longifolia leaf methanolic extract (PLME) and its underlying mechanisms. The Annexin V/PI flow cytometry analysis showed that PLME induces apoptosis in HeLa cells in dose-dependent manner whereas the PI flow cytometric analysis for cell cycle demonstrated the accumulation of cells at sub G0/G1, G0/G1 and G2/M phases. Investigation with JC-1 flow cytometry analysis indicated increase in mitochondria membrane potential depolarisation corresponding to increase in PLME concentrations. PLME was also shown to influence intracellular reactive oxygen species (ROS) by exerting anti-oxidant (half IC50) and pro-oxidant (IC50 and double IC50) affect against HeLa cells. PLME treatment also displayed DNA damage in HeLa cells in concentration depended fashion. The proteomic profiling array exposed the expression of pro-apoptotic and anti-apoptotic proteins upon PLME treatment at IC50 concentration in HeLa cells. Pro-apoptotic proteins; BAX, BAD, cytochrome c, caspase-3, p21, p27 and p53 were found to be significantly up-regulated while anti-apoptotic proteins; BCL-2 and BCL-w were found to be significantly down-regulated. This investigation postulated the role of p53 into mediating apoptosis, cell cycle arrest and mitochondrial potential depolarisation by modulating the redox status of HeLa cells.